2021
DOI: 10.3389/fimmu.2020.618327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues in Human IgM Fc Receptor (FcµR) Critical for IgM Binding

Abstract: Both non-immune “natural” and antigen-induced “immune” IgM are important for protection against infections and for regulation of immune responses to self-antigens. The roles of its Fc receptor (FcµR) in these IgM effector functions have begun to be explored. In the present study, by taking advantage of the difference in IgM-ligand binding of FcµRs of human (constitutive binding) and mouse (transient binding), we replaced non-conserved amino acid residues of human FcµR with mouse equivalents before establishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
2
10
0
1
Order By: Relevance
“…(The numbers in IgM indicate the aa position from the first N-terminal aa residue in the Cµ1 domain, not from the first Met residue that was applied for FcµR, because of variable lengths of Ig VH regions.) On the other hand, our docking model of pentameric IgM and FcµR revealed that Gln387 in the Cµ4 and to a lesser extent, Glu275 in the Cµ3 of IgM and Asn66 in the CDR2, Arg83 in the DE loop and Asn109 in the CDR3 of FcµR were all at the interface, suggesting their potential involvement in IgM binding [34]. This model was thus consistent with substantial loss of IgM binding in mutants involving removal of Asn66 or substitution of Lys79-Arg83 or Asn109 with the mouse equivalents and with the involvement of both Cµ4 and Cµ3 domains in FcµR binding [9,[37][38][39][40].…”
Section: Recent Structural Aspects Of Igm Ligandmentioning
confidence: 85%
See 1 more Smart Citation
“…(The numbers in IgM indicate the aa position from the first N-terminal aa residue in the Cµ1 domain, not from the first Met residue that was applied for FcµR, because of variable lengths of Ig VH regions.) On the other hand, our docking model of pentameric IgM and FcµR revealed that Gln387 in the Cµ4 and to a lesser extent, Glu275 in the Cµ3 of IgM and Asn66 in the CDR2, Arg83 in the DE loop and Asn109 in the CDR3 of FcµR were all at the interface, suggesting their potential involvement in IgM binding [34]. This model was thus consistent with substantial loss of IgM binding in mutants involving removal of Asn66 or substitution of Lys79-Arg83 or Asn109 with the mouse equivalents and with the involvement of both Cµ4 and Cµ3 domains in FcµR binding [9,[37][38][39][40].…”
Section: Recent Structural Aspects Of Igm Ligandmentioning
confidence: 85%
“…It was noteworthy that none of the above replacements caused significant alterations in the main-chain conformation of the receptor as determined by modeling of the substitutions or changes in the melting temperature assessed by molecular dynamics simulations. The results of receptor levels and IgM binding potential are summarized in a cartoon fashion in Figure 4, and the detailed flow cytometric data have been reported elsewhere [34].…”
Section: Site-directed Mutagenesismentioning
confidence: 96%
“…In some experiments for transductants, BD Perm/Wash Buffer was used for intracellular staining. Stained cells were examined by Becton Dickinson (BD) LSRFortessa flow cytometer along with FACSDiva software (BD Bioscience), and flow cytometric data were analyzed with Flowjo software (BD) ( 14 ). In some experiments, PBMCs isolated from healthy individuals were examined for cell surface and intracellular staining with HMD22 mAb as described ( 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Die Ergebnisse der rechnergestützten Strukturmodellierungsanalyse stimmen mit diesen Mutationsdaten überein (Abb. 1 ; [ 30 ]). Diese Erkenntnisse könnten bei der künftigen Entwicklung von präventiven und therapeutischen Maßnahmen, die auf den FcµR abzielen, hilfreich sein.…”
Section: Bedeutung Des Igm-fc-rezeptors (Fcµr) Für Die Regulation Von...unclassified